A Novel Treatment Method for Lymph Node Metastasis Using a Lymphatic Drug Delivery System with Nano/Microbubbles and Ultrasound - Kato, Shigeki (J Cancer, 2015)
Chemotherapy based on hematogenous administration of drugs to lymph nodes (LNs) located outside the surgically resected area shows limited tissue selectivity and inadequate response rates, resulting in poor prognosis. Here, we demonstrate proof of concept for a lymphatic drug delivery system using nano/microbubbles (NMBs) and ultrasound (US) to achieve sonoporation in LNs located outside the dissection area. First, we demonstrated the in vitro effectiveness of doxorubicin (Dox) delivered into three different tumor cell lines by sonoporation. Sonoporation increased the Dox autofluorescence signal and resulted in a subsequent decrease in cell viability. Next, we verified the antitumor effects of Dox in vivo using MXH10/Mo-lpr/lpr mice that exhibit systemic lymphadenopathy, with some peripheral LNs reaching 10 mm in diameter. We defined the subiliac LN (SiLN) as the upstream LN within the dissection area, and the proper axillary LN (PALN) as the downstream LN outside the dissection area. Dox and NMBs were injected into the SiLN and delivered to the PALN via lymphatic vessels; the PALN was then exposed to US when it had filled with solution. We found that sonoporation enhanced the intracellular uptake of Dox leading to high cytotoxicity. We also found that sonoporation induced extravasation of Dox from lymphatic endothelia and penetration of Dox into tumor tissues within the PALN. Furthermore, our method inhibited tumor growth and diminished blood vessels in the PALN while avoiding systemic toxic effects of Dox. Our findings indicate that a lymphatic drug delivery system with sonoporation represents a promising method for treating metastatic LNs located outside the dissection area.